2018
DOI: 10.3762/bjoc.14.122
|View full text |Cite
|
Sign up to set email alerts
|

Two new 2-alkylquinolones, inhibitory to the fish skin ulcer pathogen Tenacibaculum maritimum, produced by a rhizobacterium of the genus Burkholderia sp.

Abstract: Exploration of rhizobacteria of the genus Burkholderia as an under-tapped resource of bioactive molecules resulted in the isolation of two new antimicrobial 2-alkyl-4-quinolones. (E)-2-(Hept-2-en-1-yl)quinolin-4(1H)-one (1) and (E)-2-(non-2-en-1-yl)quinolin-4(1H)-one (3) were isolated from the culture broth of strain MBAF1239 together with four known alkylquinolones (2 and 4–6), pyrrolnitrin (7), and BN-227 (8). The structures of 1 and 3 were unambiguously characterized using NMR spectroscopy and mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Pleasingly, we found that decreasing the reaction time and temperature to one minute and 70 °C, respectively, avoided isomerization while still allowing full conversion of the starting material (entries 4 to 6). Analytical (HRMS) and spectral ( 1 H and 13 C NMR, Tables 2 and 3) data of HMAQ 1, [18][19][20][21][22]24,25,27 HMAQ 2 (burkholone), 28 and HMAQ 3 19,20,26,27 were in excellent agreement with those published for the isolated natural products.…”
Section: Scheme 2 Synthesis Of 2-(chloromethyl)-quinolone 17 Via Consupporting
confidence: 77%
See 2 more Smart Citations
“…Pleasingly, we found that decreasing the reaction time and temperature to one minute and 70 °C, respectively, avoided isomerization while still allowing full conversion of the starting material (entries 4 to 6). Analytical (HRMS) and spectral ( 1 H and 13 C NMR, Tables 2 and 3) data of HMAQ 1, [18][19][20][21][22]24,25,27 HMAQ 2 (burkholone), 28 and HMAQ 3 19,20,26,27 were in excellent agreement with those published for the isolated natural products.…”
Section: Scheme 2 Synthesis Of 2-(chloromethyl)-quinolone 17 Via Consupporting
confidence: 77%
“…The organic phase was dried over anhydrous MgSO4, filtered through Celite ® , and evaporated under reduced pressure. The crude material was purified by silica gel flash chromatography to give ethyl carbonate N-oxides (26)(27)(28). 2-(Hept-2'-en-1'-yl)-3-methylquinolin-4(1H) The reaction was stirred at rt for 1 h and then quenched with the addition of cold water (same volume as the solvent).…”
Section: Synthesis Of (E)-2-(non-2'-en-1'-yl)-3-methylquinolin-4(1h)-mentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic procedure of 1, UV, IR, 1 H NMR, 13 C NMR, COSY, HSQC, HMBC spectra for natural and synthetic 1, and UV, IR, 1 H NMR, 13 C NMR spectra for synthetic intermediates.…”
Section: Supporting Informationmentioning
confidence: 99%
“…In the course of our continuing study on bioactive metabolites of less studied bacterial taxa [13], Burkholderia sp. 3Y-MMP, isolated from soil by an exhaustive enrichment culture under Zn 2+ -load, was selected for a detailed chemical study, which resulted in the isolation of 4-hydroxy-3-methyl-2(1H)-quinolone (1, Fig.…”
Section: Introductionmentioning
confidence: 99%